THE IMPACT OF THE COVID-19 PANDEMIC AND THE EFFORT OF MSME RESURRECTION IN INDONESIA - Edy Prayitno; Nerys Lourensius Tarigan; Wahyu Eka Priana Sukmawaty; Uyuunul Mauidzoh; Deborah Kurniawati (Bajang Institute, 2021)
The COVID-19 pandemic has had a negative impact on the global economy, including Indonesia. The main victims of the COVID-19 outbreak are micro, small and medium enterprises (MSMEs). This article aims to examine the impact of the Covid-19 pandemic on MSMEs and provide recommendations that can be done to reduce business losses, survive the crisis and accelerate recovery. MSMEs were negatively affected by the Covid-19 pandemic in terms of sales, income, profits, and cash flow of business owners. MSME actors must adapt by reducing production, and reducing the number/hour of employees. More than that, product quality improvement and market expansion are important things to do. The majority of MSMEs (82.9%) in Indonesia have been negatively affected by this pandemic. Various policy recommendations were put forward to reduce the bad impact of the outbreak on MSMEs.